On Zeros of Some Combinations of Dirichlet L-Functions and Hurwitz Zeta-Functions - Garbaliauskienė, Virginija; Karaliūnaitė, Julija; Laurinčikas, Antanas (Mathematical Modelling and Analysis, 2017)
In the paper, we obtain that certain linear and more general combinations of Dirichlet L-functions and Hurwitz zeta-functions have infinitely many zeros in the critical strip. For the proof, universality of those combinations is applied.